1982
DOI: 10.1002/macp.1982.021831220
|View full text |Cite
|
Sign up to set email alerts
|

Limiting viscosity number and sedimentation coefficient of solutions of cellulose acetates

Abstract: Viscosity and sedimentation experiments were made for fractions of cellulose acetate CA (degree of substitution, D.S. = 2,46) in acetone and CA (D.S. = 2,92) in N,N-dimethylacetamide (DMAc) at 25 "C. The following empirical relations were established between the-sedimentation coefficient at infinite dilution so and the weight average molecular weight M,,,: so = 1,02 * G,$24 (s) for CA (D.S. = 2,92) in DMAc. From the analysis of the molecular weight dependence of so and the limiting viscosity number [ q ] (meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The value of cP for theCA (DS = 1. 75) fractions in DMAc depends on molecular weight as follows: (4) A similar significant molecular weight dependence of cP was found for other CA in the same solvent. It is noted that even for the •highest molecular weight fraction of CA (DS = 1.75), the cP value is about 60% smaller than the theoretical limiting value 2.87 x 10 23 for non-draining and unperturbed linear polymers and hence the draining effect is not negligible for CA (DS = 1.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The value of cP for theCA (DS = 1. 75) fractions in DMAc depends on molecular weight as follows: (4) A similar significant molecular weight dependence of cP was found for other CA in the same solvent. It is noted that even for the •highest molecular weight fraction of CA (DS = 1.75), the cP value is about 60% smaller than the theoretical limiting value 2.87 x 10 23 for non-draining and unperturbed linear polymers and hence the draining effect is not negligible for CA (DS = 1.…”
Section: Resultssupporting
confidence: 62%
“…4 -6 • 12 -14 prepared fractionated CA samples with DS equal to 0.49, 2.46, 2.92 and relatively narrow molecular weight distributions (l.!sMw/Mns1. 4; Mw and Mn are the weightand number-average molecular weights, respectively). Analysis of light scattering, membrane osmometry, viscosity, and ultracentrifugation data showed that the equilibrium chain rigidity of CA in N,N-dimethylacetamide (DMAc) depended on DS and that the unperturbed chain dimension (A) as well as the persistence length (q) become maxima at…”
mentioning
confidence: 99%
“…These results indicate that there exists specific interaction other than the van der Waals force between and solvent molecules, influencing the unperturbed chain dimensions. Up to now, 1 H NMR spectroscopy has been applied to the CA molecule for (1) determination of its configuration, 13 (2) identification of the chemical shifts of ring proton, (3) evaluation of the average combined acetic acid contentl 4 and (4) determination of the distribution of acetyl group over C2 , C 3 , and C 6 positions. 15 • 16 Nuclear magnetic resonance (NMR) spectroscopy is also expected to provide a powerful tool for studying the interaction of functional groups in cellulose derivatives and solvents.…”
mentioning
confidence: 99%
“…Method 2B: (6) Method 2C: <S2)312j M3;2 =A3 16 3!2 +(i/4n312)BM1!2 (7) (where B is the long-range interaction parameter) Method 2E: (12) where (=6-112 AcM 112 ) is the root-meansquare radius of gyration of a hypothetical freely rotating chain with Ar=0.476 x 10-8 em. The molecular weight dependence of cl> for CDA in DMAc Polymer J., Vol.…”
mentioning
confidence: 99%